Six-decades journey of CAZRI addressing arid zone crop production system in inclusive way - Yadav, O. P. (Indian Farming, 2018)
Development of technology alone won’t suffice unless there is serious involvement of various stakeholders adequately backed up by development of appropriate infrastructure along with proper policy formulation and implementation for the holistic development of the region. The Institute envisioned ‘a greener, climate resilient arid land with well-managed and sustainable agriculture that provides improved livelihood options and conserves scarce natural resources’.